(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
A magnetic micro-robot is fabricated by a stereolithographic printing technique. It only measures 3 mm in length and 1.2 mm in width. After printing, the micro-robot was coated with a sealing lacquer, containing magnetic nanoparticles. Thus, magnetic properties could be introduced and the micro-robot becomes steerable by rotating magnetic fields and visible by Magnetic Particle Imaging. A model of the middle cerebral artery containing an aneurysm was chosen. This phantom was designed from patient’s angiography and 3D-printed. The micro-robot could be successfully steered through the middle cerebral artery into the aneurysm of the phantom, demonstrating a future application scenario of treating aneurysms.